Strategi Adaptasi Mahasiswa Perantau Dalam Menghadapi Culture Shock Di Kota Jakarta (Studi Kasus Mahasiswa Di Desa Kadugadung) - Susanti, Sri Desi; Naim, Mochamad; Hayat, Nurul (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
Students in Kadugadung Village migrate to the city of Jakarta with the aim of continuing their higher education. As a result of moving to a new environment, anxiety and shock occur due to the loss of social symbols that are well known in the previous environment, so they have to re-process adaptation to their new environment. To overcome this, overseas students carry out an adaptation strategy to survive in a different environment. This study aims to determine the Adaptation Strategy of Migrant Students in Facing Culture Shock in Jakarta City. This research uses qualitative methods with descriptive methods. Data collection techniques in this study through observation, interviews, and documentation. With the focus of research, namely students in Kadugadung Village who migrated to the city of Jakarta and experienced Culture Shock. Data sources in the study were obtained from primary and secondary sources. The results showed 1) The background of culture shock in students is influenced by several aspect. 2) In adapting to the city of Jakarta, overseas students go through 4 phases including the Joy Phase, the Disappointment Phase, the Initial Resolution Phase and the last Phase Functioning Well. 3) Overseas students carry out strategies to adapt to the environment, these strategies include interaction through students and local communities, language adaptation, participating in campus organizations, and being open to new cultures